Culturable bacteria associated with Anastrepha fraterculus sp. 1 : in search of nitrogen-fixing symbionts with biotechnological potential - Salgueiro, Julieta; Nussenbaum, Ana Laura; Marchesini, María Inés; Garbalena, Micaela Soledad; Brambilla, Silvina Maricel; Belliard, Silvina Ahnahi; Cuadros, Fabián; Núñez, Mauricio; Yáñez, Carolina; Juárez, María Laura; Vera, María Teresa; Lanzavecchia, Silvia Beatriz; et al. (Wiley, 2025)
Anastrepha fraterculus is a significant fruit fly pest in Argentina and other South American countries. Previous studies showed the key role of gut bacteria in the protection and nutrient assimilation of fruit flies, particularly the importance of the biological fixation of nitrogen (diazotrophy). The presence of diazotrophic bacteria in A. fraterculus sp. 1 has been demonstrated through molecular, culture-independent methods. This study is aimed to characterize the composition and diversity of culturable gut bacteria of A. fraterculus sp. 1 males from different origins, and explore their metabolic roles, focusing on diazotrophic bacteria. Three male groups were studied: wild-caught (WW), lab-reared from wild larvae (WL), and lab-colony raised (LL). Gut bacteria were collected and characterized via 16S rRNA gene sequencing, with potential diazotrophs screened using selective media (SIL and NFb). Phylogenetic analysis of 16S rRNA gene mapped potential diazotrophs across the bacterial collection, while biochemical profiling and ARDRA (Amplified rDNA Restriction Analysis) were used to quickly differentiate diazotrophic bacteria. PCR testing for the nifH gene, associated with nitrogen fixation, was also performed. Bacterial diversity was highest in WW, followed by WL, and lowest in LL. In LL and WL, Enterobacter was the most frequent genus, while Klebsiella dominated in WW. Among the 20 SIL+ isolates identified, 10 came from WW, 9 from WL, and 1 from LL. One of these isolates (Enterobacter sp.) was tested as a supplement to the adult diet, without showing a beneficial effect on males pheromone calling behavior. Three isolates were also NFb+; two had the nifH gene. ARDRA was effective for rapid diazotroph discrimination. These findings highlight the potential of gut symbiotic bacteria in eco-friendly pest management strategies like the sterile insect technique (SIT). By using diazotrophic bacteria, protein requirements in artificial diets could be reduced, cutting costs and improving the affordability of SIT programs.